Escherichia coli Culture Filtrate Enhances the Growth of Gemmata spp. - Kaboré, Odilon D.; Aghnatios, Rita; Godreuil, Sylvain; Drancourt, Michel (Frontiers in Microbiology, 2019)
Background: Planctomycete bacteria are known to be difficult to isolate, we hypothesized this may be due to missing iron compounds known to be important for other bacteria. We tested the growth-enhancement effect of complementing two standard media with Escherichia coli culture filtrate on two cultured strains of Gemmata spp. Also, the acquisition of iron by Gemmata spp. was evaluated by measuring various molecules involved in iron metabolism. Materials and Methods: Gemmata obscuriglobus and Gemmata massiliana were cultured in Caulobacter and Staley's medium supplemented or not with E. coli culture filtrate, likely containing siderophores and extracellular ferrireductases. We performed iron metabolism studies with FeSO4, FeCl3 and deferoxamine in the cultures with the E. coli filtrate and the controls. Results and Discussion: The numbers of G. obscuriglobus and G. massiliana colonies on Caulobacter medium or Staley’s medium supplemented with E. coli culture filtrate were significantly higher than those on the standard medium (p<0.0001). Agar plate assays revealed that the Gemmata colonies near E. coli colonies were larger than the more distant colonies, suggesting the diffusion of unknown growth promoting molecules. The inclusion of 10-4 to 10-3 M FeSO4 resulted in rapid Gemmata spp. growth (4-5 days compared with 8-9 days for the controls), suggesting that both species can utilize FeSO4 to boost their growth. In contrast, deferoxamine slowed down and prevented Gemmata spp. growth. Further studies revealed that the complementation of Caulobacter medium with E. coli culture filtrate and 10-4 M FeSO4 exerted a significant growth-enhancement effect compared with that obtained with Caulobacter medium supplemented with E. coli culture filtrate alone (p<0.0122). Moreover, the intracellular iron concentrations in G. obscuriglobus and G. massiliana cultures in iron-depleted broth supplemented with the E. coli filtrate were 0.63 ± 0.16 µmol/L and 0.78 ± 0.12 µmol/L, respectively, whereas concentrations of 1.72 ± 0.13 µmol/L and 1.56 µmol/L ± 0.11 µmol/L were found in the G. obscuriglobus and G. massiliana cultures grown in broth supplemented with the E. coli filtrate and FeSO4. The data reported here indicated that both E. coli culture filtrate and FeSO4 act as growth factors for Gemmata spp. via a potentiation mechanism.